GC-MS ANALYSIS OF TERPENOIDS FROM LEAVES OF Canarium odontophyllum Miq.(DABAI) - Muhammad Wahizul Haswan, Abdul Aziz; Siti Fathiah, Masre; Dayang Fredalina, Basri; Ahmad Rohi, Ghazali (Institut Penyelidikan Perhutanan Malaysia, 2021)
Terpenoids are defined as secondary metabolites with carbon backbone molecular structures consisting of isoprene (2-methylbuta-1, 3-diene) units. They demonstrate important biological activities, such as antibacterial, antiviral, antimalarial, antiinflammatory, anticancer and cholesterol synthesis inhibition activities. Canarium odontophyllum Miq. or locally known as “dabai” is an endemic plant in Sarawak, Malaysia. Its leaf compositions were examined by using the GC-MS analysis in order to compare and contrast their volatile terpenoids constituents. The terpenoids content were 36.67% and 14% for hexane and ethanol extracts, respectively. nHexadecanoic acid, phytol and octadecanoic acid were the major terpenoids constituents from the leaves of C. odontophyllum Miq. n-Hexadecanoic acid (20.22%), phytol (8.74%) and octadecanoic acid (7.54%) were found to be predominant in the hexane extract, while phytol(21.02%) and n-hexadecanoic acid (14.52%) were major constituents in the ethanol extract. The C.odontophyllum Miq. leaf constituents are also related to their biological activities and would offer promising therapeutic effects. Further investigation should be conducted to develop it as apotential therapeutic drug.